Pyogenic Granuloma of the Larynx: A Case Report - Moallim Hussein AA; Sheikh OA; Mukhtar AA; Abdi IA; Ahmed NM; Mohamed SS; Kahiye MA; Nur MA; Asseyr AF (International Medical Case Reports Journal)
Abdullahi Ali Moallim Hussein,1 Omar Adam Sheikh,2 Abdiwahab Abdirahman Mukhtar,3 Intisar Ahmed Abdi,4 Nasra Mohamed Ahmed,5 Shukri Said Mohamed,6 Mohamed Ali Kahiye,7 Mohamed Abdikarim Nur,8 Abdullahi Farah Asseyr9 1Department of Otorhinolaryngology, Welcare Specialty Hospital, Mogadishu, Somalia; 2Department of Basic Medical Sciences, Faculty of Medicine, Somali National University, Mogadishu, Somalia; 3Department of Otorhinolaryngology, Port Elizabeth Provincial Hospital, Eastern Cape, South Africa; 4Department of Anesthesia, Welcare Specialty Hospital, Mogadishu, Somalia; 5Department of Clinical Sciences, Faculty of Medicine and Surgery, Somali National University, Mogadishu, Somalia; 6Department of Pediatric Surgery, Mogadishu Somali Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia; 7Department of Pathology, Sahan Pathology Lab, Mogadishu, Somalia; 8Department of Surgery, Faculty of Medicine and Surgery, Somali National University, Mogadishu, Somalia; 9Department of Pediatrics and Neonatology, Welcare Specialty Hospital, Mogadishu, SomaliaCorrespondence: Omar Adam Sheikh, Department of Basic Medical Sciences, Faculty of Medicine and Surgery, Somali National University, 21 October Road, Waberi, Mogadishu, Somalia, Tel +252615950095, Email qooje@snu.edu.soIntroduction: Pyogenic granulomas are benign, painless vascular tumors on the skin and mucosal surfaces. They are commonly found in the head and neck region, although their occurrence in the larynx is rare. The term “lobular capillary hemangioma” is now used to describe the histological appearance of these tumors more accurately. Predisposing factors for pyogenic granuloma of the larynx have been linked to prior traumatic injuries, such as intubation, previous surgeries, or laryngopharyngeal reflux.Case Presentation: A 33-year-old male visited our clinic with complaints of progressive dysphonia and choking for two months. The patient did not experience dysphagia or dyspnea. There was no history of previous intubation, gastroesophageal reflux disease, or other chronic illnesses. Upon laryngoscopic examination, a polypoid lesion measuring 25× 8 mm was found on the posterior commissure of the right vocal cord. No abnormalities were observed during the ear and nose examinations.Discussion: Pyogenic granuloma, or lobular capillary hemangioma, is a hyperplastic lesion that develops on the skin and mucous membranes. It often occurs in response to trauma or hormonal factors. Histologically, pyogenic granulomas differ from granulation tissues due to their lobular arrangement of capillaries in the deeper portions of the lesion. The term “lobular capillary hemangioma” has been recently introduced to emphasize this phenomenon. Some of the conditions considered in the differential diagnosis include hemangioma, hemangioendothelioma, angiofibroma, angiosarcoma, Kaposi sarcoma, Wegener’s granuloma, Crohn’s disease, granulomatous infections such as tuberculosis and histoplasmosis, traumatic granuloma, carcinosarcoma, as well as verrucous and squamous cell carcinoma.Conclusion: We present a case report of lobular capillary hemangioma of the larynx, including its histopathological diagnosis and management course.Keywords: vocal cord, laryngoscope, hemangioma, bartonella